Factors Associated With Colon and Rectal Surgery Fellowship Program Ranking Before and After the COVID-19 Pandemic. Issue 10 (October 2021) - Goffredo, Paolo; Sun, Mark Y.; Jensen, Christine C.; Trudel, Judith L.; Madoff, Robert D.; Lowry, Ann C.; Gaertner, Wolfgang B.
Abstract : Supplemental Digital Content is available in the text.